2021
DOI: 10.3102/0091732x20985069
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Disability: High-Quality Evidence in Research on Special Education Disproportionality

Abstract: This chapter examines how studies focused on the same topic—disproportionality in special education—can generate vastly different conclusions about its sources and causes. By analyzing existing disagreements in the field, we explore essential questions about what constitutes high-quality and relevant evidence when seeking to understand how, when, for whom, and why disproportionality occurs. Using a holistic review of the empirical literature on disproportionality, we illustrate how differing epistemological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 188 publications
(223 reference statements)
0
9
0
2
Order By: Relevance
“…5. (Ahram et al, 2021) Comprensión de la discapacidad: evidencia de alta calidad en la investigación sobre la desproporcionalidad de la educación especial.…”
Section: Aplicaciones Móvilesunclassified
See 1 more Smart Citation
“…5. (Ahram et al, 2021) Comprensión de la discapacidad: evidencia de alta calidad en la investigación sobre la desproporcionalidad de la educación especial.…”
Section: Aplicaciones Móvilesunclassified
“…No menos importante la consulta del artículo publicado por (Ahram et al, 2021), quienes muestran como antes del año 2020, existe muy poca la información que se puede consultar publicada en revistas indexadas de alta calidad científica. Adicionalmente a lo plasmado, este estudio ha permitido establecer las variables con efecto significativo en el proceso académico de esta población y con fundamento en lo identificado, plantear soluciones.…”
Section: Introductionunclassified
“…In both special education labeling and school discipline practices, there are embedded scripts that actors within the educational system follow (Ahram et al, 2011;Bal et al, 2019;Banks, 2017;Fish, 2017;Kozleski et al, 2008;Lambert, 2018). There are multiple points at which bias can be introduced (Ahram et al, 2021;Okonofua & Eberhardt, 2015;Smolkowski et al, 2016), and policies (Kramarczuk Voulgarides, 2018) and structures (Elder et al, 2019;Fish, 2019;Ray, 2019) also affect practitioners' decisions and perpetuate inequities. For example, Fish (2019) found that school racial composition was linked to the likelihood that African American students would be sorted into more subjective and stigmatizing disability categories.…”
Section: Analysis In a Quantcrit Perspectivementioning
confidence: 99%
“…Qualitative work on disproportionality has highlighted the manner in which deficit ideologies are embedded in school systems (Bal et al, 2014; Harry et al, 2005; Lambert, 2019; Leonardo & Broderick, 2011; Lewis-McCoy, 2016) and the ways in which disparate discipline and labeling practices affect students’ and families’ lived experiences (Annamma et al, 2019; Banks, 2017; Connor et al, 2019). However, quantitative and qualitative works often speak past one another in attempts to uncover complexities that are subject to agency–structure dualism ; individual actors within schools can enact agency, but outcomes remain subject to embedded structural inequities (Ahram et al, 2021; Mehan, 1992). Both discipline and special education identification represent processes that are subject to the agency–structure divide, and there are multiple points in each process at which bias may be introduced (see Smolkowski et al, 2016, for discipline, and Artiles, 2019, for special education).…”
mentioning
confidence: 99%
“…The inequities are the result of a confluence of factors related to, but not limited to: (a) punitive discipline policies and practices; (b) inadequate interventions and referrals; (c) inadequate instruction and assessment; (d) differential access to educational opportunities; (e) weak family and community partnerships with schools; (f) misguided teacher expectations and misconceptions; (g) cultural dissonance, biases and institutional racism and ableism due to white and ability supremacy and; (h) changing district sociodemographic contexts (Iqtadar et al, 2020;Marsico, 2022;Skiba, et al, 2008;Voulgarides et al, 2013). The sources, causes, and magnitude of the disparities are extremely complex (Ahram et al, 2021;Artiles, 2019;Shifrer & Fish, 2020), and future educational leaders must be prepared to address these systemic racist and ableist challenges through a justice and equity-oriented educational policy lens.…”
mentioning
confidence: 99%